Methods for 3D digitization of Cultural Heritage - Pavlidis, George; Koutsoudis, Anestis; Arnaoutoglou, Fotis; Tsioukas, Vassilios; Chamzas, Christodoulos (Journal of cultural heritage, 2007)
Complete digital recording of Cultural Heritage is a multidimensional process. It depends highly on the nature of the subject of recording as well as the purpose of its recording. The whole process involves the three-dimensional digitization, digital data processing and storage, archival and management, representation and reproduction. In this paper we briefly review methods for three-dimensional digitization that are applicable to cultural heritage recording.